How Big Data Analytics, AI, and Social Media Marketing Research Boost Market Orientation: Companies can use big data analytics, artificial intelligence (AI), and social media marketing research to increase market orientation. Issue 2 (22nd February 2022) - Zhang, Haili; Song, Michael
ABSTRACT: Overview: Previous research has shown that market-oriented firms outperform their peers. Why are some firms such outstanding performers in market orientation (MO)? This study identifies three categories of new technology tools that have emerged in the past few years—big data analytics, artificial intelligence (AI), and social media marketing research—and assesses how each category enhances MO. The empirical evidence from 442 firms indicates that all three categories have significant impacts on MO, with AI being the most effective, followed by big data analytics and social media marketing research, respectively. We outline how very successful firms adopt these new technology tools and offer managerial implications that can guide senior executives looking to increase MO.